ANALYSIS OF MULTICULTURAL CURRICULUM ON ENHANCING STUDENTS' TOLERANCE AND GLOBAL AWARENESS - Sholeh, Muh Ibnu; Sokip; Habibulloh, Muh; Al Farisy, Fakhruddin; Ali, Himad (INTIHA: Islamic Education Journal, 2025)
This study explores the impact of multicultural curricula on students' tolerance and global awareness in Indonesia. As a country characterized by rich cultural, ethnic, and religious diversity, Indonesia requires a strong multicultural education framework to foster an inclusive and harmonious society. Adopting a literature review approach, this research examines academic sources, policy documents, and educational reports published in the last decade to ensure relevance and accuracy. Data collection was conducted through an extensive literature search across various academic databases, including Google Scholar, JSTOR, ProQuest, and Scopus, as well as local sources discussing the implementation of multicultural education policies and the challenges faced by schools in Indonesia. The collected data was analyzed qualitatively using a descriptive-analytical approach. The findings reveal that multicultural curricula play a significant role in enhancing students' understanding of cultural diversity and instilling values of tolerance and social justice. However, challenges remain in its implementation, particularly due to teachers' limited understanding of multicultural education and insufficient policy support. To address these issues, stronger efforts from the government and educational institutions are necessary, including comprehensive teacher training programs and the development of clear, practical guidelines for multicultural education. This study contributes to the advancement of inclusive educational policies aimed at preparing students to navigate global challenges in an increasingly interconnected world.